Analysis of Steel Refining in Pony Ladle - Efimova, V. G.; Єфімова, В. Г. (Springer Nature, 2020)
The basic laws of ballistic motion are used to calculate the following in coordinate form: the residence time of a metal droplet in slag with adsorbed nonmetal impurities (NMIs) with the inert gas blowing of liquid steel in a CC machine’s pony ladle. These data can be used to set the optimal speed of eliminating NMIs from the metal in the pony ladle at different gas consumption rates, as well as the plausible diameter of gas bubbles. The eliminations of the NMIs in the pony ladle using extended blowoff tuyeres were compared for efficiency during industrial tests. The NMI content was estimated by technique K4 under DIN 50602- 1985. The theoretical calculation of the optimal inert gas consumption for the metal blowoff through an extended multichannel tuyere was made, the surpassing of which weakens the refining effect due to the slag capture in liquid melt.
Keywords: pony ladle; CC machine; nonmetal impurities; residence time; extended blowoff tuyere; slag phase; refining